Effect of lipopolysaccharide on the biological characteristics of human skin fibroblasts and hypertrophic scar tissue formation1. Issue 6 (7th May 2013) - Yang, Hongming; Hu, Chao; Li, Fengyu; Liang, Liming; Liu, Lingying
Abstract Burn injury‐mediated destruction of the skin barrier normally induces microbial invasion, in turn leading to the development of systemic infection and occasional septic shock by the release of endotoxins. The objective of this work was to study the influence of lipopolysaccharide (LPS) on the biological characteristics of normal skin fibroblasts and to elucidate the influence of LPS in the initial stage of skin wound healing. Twenty patients with hypertrophic scar in proliferative stage were selected randomly and primary cultures were established from fibroblasts derived from their hypertrophic scar tissue and normal skin. Normal skin fibroblasts of passage 3 were stimulated with different concentrations of LPS. LPS stimulated the proliferation and collagen synthesis of fibroblasts within a certain extent of concentrations (0.005–0.5 μg/mL) (P < 0.05), whereas at a concentration of 1 μg/mL inhibited the proliferation and collagen synthesis of fibroblasts (P < 0.05). Collagen synthesis by normal skin fibroblasts after LPS stimulation mimicked those derived from hypertrophic scar tissue. LPS of 0.1 μg/mL had significant effect on normal skin fibroblasts—continuous passage of these fibroblasts resulted in ultrastructural pattern similar to fibroblasts derived from hypertrophic scar tissue, and the findings was substantiated by hematoxylin and eosin staining and immunohistochemistry detection of proliferation cell nuclear antigen, type I procollagen and α‐smooth muscle actin. Our results suggest that LPS might convert normal skin fibroblasts to hypertrophic scar tissue fibroblasts and participate in the formation of hypertrophic scar; hence, appropriate concentration of LPS may have no effect or be beneficial to skin wound healing, whereas excessive concentration of LPS may delay the time of wound healing. © 2013 IUBMB Life, 65(6):526–532, 2013.